Loperamide toxicity: recommendations for patient monitoring and management. (3rd May 2020) - Eggleston, William; Palmer, Robert; Dubé, Pierre-André; Thornton, Stephen; Stolbach, Andrew; Calello, Diane P; Marraffa, Jeanna M
Abstract: Who: This position statement is a collaborative effort by the American Academy of Clinical Toxicology (AACT) and the American Association of Poison Control Centers (AAPCC) and has been endorsed by the American College of Medical Toxicology (ACMT). The position statement describes loperamide misuse, proposed mechanisms of toxicity, adverse clinical effects, and recommendations for the acute monitoring and management of patients with loperamide toxicity. Why: Use of high-dose loperamide for its euphoric effects and to self-treat opioid use disorder (in place of evidence-based therapies, like buprenorphine or methadone), is increasing. Despite reports in the medical literature and lay press, many remain unaware of high-dose loperamide use and how to manage patients with loperamide-associated toxicities. Target audience: Providers in Emergency Medicine; Prehospital; Intensive Care; Internal Medicine; Primary Care; Gastroenterology; Addiction Medicine; Pharmacy